An economic evaluation of risankizumab versus other biologic treatments of moderate to severe plaque psoriasis in Japan. (2nd January 2022) - Saeki, Hidehisa; Ishii, Kanako; Joshi, Avani; Bensimon, Arielle G.; Yang, Hongbo; Kawaguchi, Isao
Abstract: Objective: To evaluate the cost-effectiveness of risankizumab versus other biologic treatments (adalimumab, infliximab, ustekinumab, secukinumab, brodalumab, ixekizumab, and guselkumab) of moderate-to-severe psoriasis in Japan. Methods: A Markov cohort-level model was constructed to estimate quality-adjusted life years (QALYs) and costs for each treatment over a lifetime horizon. The model simulated patients' transition through one line of active biologic therapy followed by best supportive care and death. Transition probabilities were informed by network meta-analyses of Psoriasis Activity and Severity Index responses and adverse event-related discontinuation in clinical trials, as well as published real-world evidence and national mortality rates. Costs were evaluated from the health system, societal, and patient out-of-pocket perspectives. Results: Risankizumab was expected to provide 0.30–0.89 additional QALYs versus comparator biologics. Under the health system perspective, incremental cost-effectiveness ratios (ICERs) of risankizumab ranged from ¥2, 545, 812/QALY versus ustekinumab to ¥6, 077, 134/QALY versus adalimumab. Societal ICERs were lower, ranging from ¥921, 770/QALY to ¥4, 350, 879/QALY. From the patient perspective, risankizumab was estimated to be cost-saving versus four comparators and was associated with ICERs of <¥500, 000/QALY versus the remaining comparators. Conclusion: Risankizumab was associated with higher QALYs and, based on typical willingness-to-pay benchmarks (¥5-6.7 million/QALY), considered cost-effective versus other biologics for the treatment of psoriasis in Japan.